2022
DOI: 10.1590/fst.51221
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide regulates DNMT1-mediated methylation of VDR promoter to relieve podocyte damage in mice with diabetic nephropathy

Abstract: Current evidence showed that parthenolide (PN) has strong anti-inflammatory activity, but its effect on diabetic nephropathy (DN) is still unclear. In this research, high glucose (HG)-induced MPC5 cells were incubated with 5, 10 or 20 μM PN, and we found that PN incubation improved HG-induced MPC5 cells viability and apoptosis, ROS level, LDH activity and the secretion of inflammatory factors (IL-6, TNF-α and IL-1β), and inhibited the expression of DNMT1 protein, and promoted the expression of VDR, p-AKT, neph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Physiological characteristics are glucose intolerance, obesity, hypertension and premature atherosclerosis (Muche et al, 2020). Damage to other organs is manifested as acute pancreatitis, diabetic nephropathy, diabetic peripheral neuropathy, such as insulin resistance, hypertension and dyslipidemia (Yang et al, 2022a). These changes are also associated with oxidative (Krycer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological characteristics are glucose intolerance, obesity, hypertension and premature atherosclerosis (Muche et al, 2020). Damage to other organs is manifested as acute pancreatitis, diabetic nephropathy, diabetic peripheral neuropathy, such as insulin resistance, hypertension and dyslipidemia (Yang et al, 2022a). These changes are also associated with oxidative (Krycer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In a cellular context, parthenolide significantly improved high glucose-induced apoptosis and inflammation in MPC5 cells, a podocyte cell line. It was also observed to increase the expression levels of matrix-related proteins such as nephrin and podocin, key elements in maintaining podocyte integrity ( Yan et al, 2022 ).…”
Section: Natural Bioactive Compounds Targeting Vdr Activitymentioning
confidence: 99%
“…Parthenolide has shown potential as a DNA methylation inhibitor—it was observed to inhibit DNA methyltransferase 1 (DNMT1) ( Liu et al, 2009 ), a noteworthy effect considering DNMT1 was found to be upregulated in diabetic nephropathy mice and high glucose-induced MPC5 cells ( Yan et al, 2022 ). This upregulation contributes to the hypermethylation of the VDR gene, which is significantly associated with lower VDR gene expression levels and vitamin D levels ( Guan et al, 2022 ).…”
Section: Natural Bioactive Compounds Targeting Vdr Activitymentioning
confidence: 99%